1992
DOI: 10.1073/pnas.89.17.8107
|View full text |Cite
|
Sign up to set email alerts
|

A mitogenic peptide amide encoded within the E peptide domain of the insulin-like growth factor IB prohormone.

Abstract: We have identified an amino acid sequence within the E peptide of the insulin-like growth factor IB (IGF-IB) precursor that is biologically active and designated this peptide insulin-like growth factor IB-(103-124) E1 amide (IBEl). Its existence was predicted by a flanking Gly-Lys-LysLys, a signal sequence for sequential proteolytic cleavage and peptidyl C-terminal amidation. A synthetic analog of the predicted IBE, peptide, designated Y-23-R-NH2, was generated with tyrosine added at position 0. This peptide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
100
0
6

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 33 publications
6
100
0
6
Order By: Relevance
“…Recently, Mark Chen in Taiwan also demonstrated that Ea2-peptide of zebrafish exerted a stimulatory effect on incorporation of 35 S-sulfate into zebrafish gill bronchial cartilage in a sulfation assay (personal communication). These results are consistent with those reported in mammals (Siegfried et al, 1992;Matheny et al, 2010;Yang and Goldspink 2002). Further studies conducted in our laboratory showed that both recombinant rtEa4-or synthetic hEbpeptide exerted unexpected anti-cancer cell activities in established human cancer cell lines such as MDA-MB-231, HT-29, HepG2, SK-N-F1, SKOV-3A, PC-3 and OVCAR-3B (Chen et al, , 2007Kuo and Chen 2002).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Recently, Mark Chen in Taiwan also demonstrated that Ea2-peptide of zebrafish exerted a stimulatory effect on incorporation of 35 S-sulfate into zebrafish gill bronchial cartilage in a sulfation assay (personal communication). These results are consistent with those reported in mammals (Siegfried et al, 1992;Matheny et al, 2010;Yang and Goldspink 2002). Further studies conducted in our laboratory showed that both recombinant rtEa4-or synthetic hEbpeptide exerted unexpected anti-cancer cell activities in established human cancer cell lines such as MDA-MB-231, HT-29, HepG2, SK-N-F1, SKOV-3A, PC-3 and OVCAR-3B (Chen et al, , 2007Kuo and Chen 2002).…”
supporting
confidence: 81%
“…Third, different isoforms of pro-IGF-I transcripts are expressed in a tissue-specific and developmental stage-specific manner, and exhibiting differential responses to growth hormone (Shamblott and Chen 1993;Duguay 1994;Yang and Goldspink 2002). Siegfried et al (1992) reported the first evidence that hEbpeptide contained biological activity. In their studies, Siegfried and colleagues showed that a synthetic peptide amide with 23 amino acid residues (Y-23-R-NH 2 ) of the hEb-peptide (a.a. 103-124) at 2-20 nM exerted mitogenic activity in normal and malignant human bronchial epithelial cells.…”
mentioning
confidence: 99%
“…Furthermore, our data documented that a synthetic MGF E-peptide can stimulate the proliferation of human KLE cells, an endometrial carcinoma cell line with a phenotype of endometrial-like cells, via an IGF-1R-independent and IR-independent mechanism. These data suggest that a 4, and it is responsible for binding with the IGF receptors and different E-domain products (Figure 1), which contain different parts of exon 5 and/or exon 6 (8)(9)(10)(11) and have been proposed to act autonomously (8,12).…”
Section: Subjectsmentioning
confidence: 99%
“…It may be responsible for both mitogenic (26) and inhibitory effects on cancer cell growth (27). Furthermore, peptide Eb, which is composed of Eb1 and Eb2 peptides may exert mitogenic effects on IGF-1 independently; however, the activity of both peptides differs in various types of tissue (28). Peptide Ec (MGF) was originally identified in the liver, while higher amounts have been found in muscle following training (29,30).…”
Section: Differential Expression Of Igf-1 Mrna Isoforms In Colorectalmentioning
confidence: 99%